Proximally Based Medial Hemi-Soleus Muscle Flap Employed For Moderate-Sized Pretibial Defects of the Middle Third of the Leg - Saaiq, Muhammad; Ullah, Irfan; ullah, Ikram (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES This study was undertaken to document the clinical indications and outcome of proximally based medial Hemi-soleus muscle flap for coverage of moderate-sized complex pretibial defects of the middle third of the leg. METHODOLOGY This descriptive case series was conducted at the Department of Plastic Surgery, National Institute of Rehabilitation Medicine (NIRM), Islamabad and Burn & Trauma Center, Hayatabad, Peshawar, over five years. (i.e., from November 01, 2016, to December 31, 2021). It included all adult patients of either gender whose complex pretibial wounds of the middle third leg were managed with proximally based medial Hemi-soleus muscle flaps. RESULTS The mean age was 31.40±9.83 years, ranging between 19-47 years. All the patients had complex post-traumatic defects secondary to road traffic accidents. There were 9(33.3%) patients with minor defects (i.e., measuring ≤2×2 cm2), whereas 18(66.6%) patients had medium-sized defects (i.e., ≥2×2 cm2 and ≤7×5 cm2). Their hospital stay ranged between 9-15 days with a mean stay of 11.92±3.1 days. All the flaps (100%) survived. Partial skin graft loss was encountered among three patients (n=3;11.1%). CONCLUSION The study provides a good evidence base regarding the usefulness of the flap in managing complex defects of the leg. It is recommended to carry out similar studies internationally. These should help improve our findings and come up with further refinements.